Genetic and clinical features of pediatric-onset hereditary spastic paraplegia: a single-center study in Japan - Ikeda, Azusa; Kumaki, Tatsuro; Tsuyusaki, Yu; Tsuji, Megumi; Enomoto, Yumi; Fujita, Atsushi; Saitsu, Hirotomo; Matsumoto, Naomichi; Kurosawa, Kenji; Goto, Tomohide (Frontiers in Neurology, 2023)
Background and purpose Hereditary spastic paraplegias (HSPs) are a set of heterogeneous neurodegenerative disorders characterized by bilateral lower limb spasticity. They may present from infancy onwards at any time. Although next-generation sequencing has allowed the identification of many causative genes, little is known about which genes are specifically associated with pediatric-onset variants. Methods This study retrospectively evaluated the genetic analyses, family history clinical courses, magnetic resonance imaging (MRI) findings, and electrophysiologic findings of patients diagnosed with HSP in childhood at a tertiary pediatric hospital in Japan. Genetic analyses were performed using direct sequencing, disease-associated panels, and whole-exome sequencing. Results Of the 37 patients included, 14 had a family history of HSP and 23 had a sporadic form of the disease. In 20 patients, HSP was the pure type, whereas the remaining 17 patients had complex types of HSP. Genetic data were available for 11 of the pure-type patients and 16 of those with complex types. Of these, genetic diagnoses were possible in 5 (45%) of the pure-type and 13 (81%) of the complex-type patients. SPAST variants were found in five children, KIF1A variants in four, ALS2 variants in three, SACS and L1CAM variants in two each, and an ATL1 variant in one. One child had a 10p15.3p13 duplication. Four patients with pure-type HSPs had SPAST variants and one had an ALT1 variant. The KIF1A, ALS2, SACS, and L1CAM variants and the 10p15.3p13 duplication were seen in children with complex-type HSPs, with just one complex-type patient having a SPAST variant. The identification of brain abnormalities on MRI was significantly more common among children with complex-type (11 [69%] of 16) than pure-type HSPs (one [5%] of 19) (p < 0.001). Scores on the modified Rankin Scale for Neurologic Disability were also significantly higher among children with complex-type compared with pure-type HSPs (3.5 ± 1.0 vs. 2.1 ± 0.9, p < 0.001). Conclusion Pediatric-onset HSP was found to be sporadic and genetic in a substantial proportion of patients. The causative gene patterns differed between children with pure-type and complex-type HSPs. The causative roles of SPAST and KIF1A variants in pure-type and complex-type HSPs, respectively, should be explored further.